Study on the prediction of short-term clinical changes after cerebral infarction using carotid plaque ultrasound strain elastography - Li, Mingqiu; Weng, Shiwen; Song, Qian; Ge, Huiyu (Frontiers in Neurology, 2025)
ObjectiveTo evaluate the value of ultrasound strain elastography in assessing carotid plaque stiffness for predicting short-term clinical changes after cerebral infarction.MethodsPatients with cerebral infarction and carotid atherosclerotic plaque identified through routine ultrasound examination at the Ultrasound Department of Beijing Chaoyang Hospital, Capital Medical University, were selected for this study. All patients underwent strain elastography. Based on changes in their clinical conditions within 30 days following cerebral infarction, they were divided into a deterioration group and a non-deterioration group. The differences between the two groups in terms of strain elastography results were compared for statistical significance. Logistic regression analysis was conducted to analyze factors affecting short-term clinical changes in patients with cerebral infarction. The receiver operating characteristic (ROC) curve was drawn.ResultsA total of 110 patients were included in this study (83 males and 27 females, average age: 60.02 ± 10.67 years). The carotid plaque strain elastography value, arterial wall strain elastography value and plaque stiffness were1.17 ± 0.40, 0.53 ± 0.16 and 2.33 ± 0.97 in the deterioration group, 1.73 ± 0.58, 0.59 ± 0.18 and 3.04 ± 1.00 in the non-deterioration group. The differences between the two groups were statistically significant about carotid plaque strain elastography value and plaque stiffness. The AUC values for predicting non-deterioration after cerebral infarction were 0.790 for carotid plaque strain elastography value, 0.608 for arterial wall strain elastography value, and 0.740 for plaque stiffness.ConclusionCarotid plaque ultrasound strain elastography can be utilized to assess short-term clinical changes after cerebral infarction. Patients who experience clinical deterioration have lower carotid plaque strain elastography values, indicating that this parameter is more effective in predicting the absence of deterioration after cerebral infarction.